Diagnosis of primary ciliary dyskinesia: potential options for resource-limited countries. (18th January 2017) - Rumman, Nisreen; Jackson, Claire; Collins, Samuel; Goggin, Patricia; Coles, Janice; Lucas, Jane S.
Primary ciliary dyskinesia is a genetic disease of ciliary function leading to chronic upper and lower respiratory tract symptoms. The diagnosis is frequently overlooked because the symptoms are nonspecific and the knowledge about the disease in the primary care setting is poor. Additionally, none of the available tests is accurate enough to be used in isolation. These tests are expensive, and need sophisticated equipment and expertise to analyse and interpret results; diagnosis is therefore only available at highly specialised centres. The diagnosis is particularly challenging in countries with limited resources due to the lack of such costly equipment and expertise. In this review, we discuss the importance of early and accurate diagnosis especially for countries where the disease is clinically prevalent but diagnostic tests are lacking. We review the diagnostic tests available in specialised centres (nasal nitric oxide, high-speed video microscopy, transmission electron microscopy, immunofluorescence and genetics). We then consider modifications that might be considered in less well-resourced countries whilst maintaining acceptable accuracy. PCD diagnosis with limited resources http://ow.ly/eYN7302Y2wg